Kontribusi Komponen Proses Pendidikan dan Mutu Lulusan PTAI Terhadap Kepuasan Masyarakat - Abdul Haris Abdullah; Shinta Nento (Jurnal Ilmiah Iqra', 2011)
This study aims to measure the contribution of the education process and the quality of graduates of the PTAI community satisfaction. The method is a survey research, data processing with software SPSS 14 for windows. Results showed there were positive and significant contribution either individually or jointly educational process and quality of graduates of community satisfaction.Keywords: Community Satisfaction, Contribution Process and Quality Graduates